Patterns and Outcome of Poisoning Case Admitted in ICU of Provincial Hospital of Bagmati Nepal (Nepal Journal of Health Sciences, 2025)
Introduction: Poisoning is a serious public health issue that can be caused by numerous chemical and pharmacological substances. It is one of the causes of patient admission in Intensive Care Unit. Poisoning has a harmful effect due to exposure to a foreign chemical. A proper assessment, appropriate management and immediate treatment in intensive care unit is necessary for better outcome.Objectives: To describe the patterns of admission and outcome of poisoning case admitted in Intensive Care Unit of Provincial Hospital of Bagmati Nepal.Methods: A retrospective cross-sectional study was conducted and data from November 2022 to November 2023 was collected from the Intensive Care Unit logbook record and chart .Results: Total of 77 patients were admitted with poisoning during 12 months of study period. The mean age of the patients is 32 ± 19 years. Most common age group of poisoning was between 16-45 years. Most of the patient admitted in Intensive Care Unit with diagnosis of poisoning were married 52 (67.5%). Insecticide (55.8%) was the most commonly ingested poison. Most of the cases were suicidal attempts due to family disharmony. Most of the patients 55 (71.4%) completely recovered and discharged while 6 (7.8%) expired at hospital and 2 (2.6%) patients were referred to higher center for further management.Conclusion: The majority of poisoning cases included females between the ages of 16 and 45 who were married and had attempted suicide as a result of family trouble. The most often consumed toxin was insecticide (55.8%) and organophosphorus compound is the most common insecticides used.